Use of lac fusions to measure in vivo regulation of expression of Escherichia coli proton-translocating ATPase (unc) genes. - Angov, E (1988)
In-frame fusions to lacZ were constructed in two adjacent genes of the unc operon of Escherichia coli, uncA and uncG, which code for the alpha and gamma subunits of the proton-translocating ATPase. After each fusion was moved into the E. coli chromosome, measurement of beta-galactosidase activities from single-copy genes showed that uncA was expressed significantly better in vivo than was uncG, but the relative expression dependent on the chromosomal location of each fusion and the presence or absence of other unc genes.